2009
DOI: 10.1097/inf.0b013e3181a3242e
|View full text |Cite
|
Sign up to set email alerts
|

Cat Scratch Disease With Cervical Vertebral Osteomyelitis and Spinal Epidural Abscess

Abstract: Cat scratch disease has variable clinical presentations and should be considered in the differential diagnosis of vertebral osteomyelitis and epidural abscess if there is a history of contact with cats. We report a 5-year-old boy with cat scratch disease who presented with painful torticollis and osteomyelitis of the cervical spine associated with an epidural abscess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…1,10 Duration of intravenous antibiotic therapy should be a minimum of 4 to 6 weeks. 6 The length of therapy is dependent on the level of immunocompetence, clinical improvement, and response to treatment demonstrated by subsequent ESR and MRI. 8 The typical treatment of SEA is surgical decompression and drainage in combination with several weeks of antibiotics, 4,13,26 although no consensus on management has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,10 Duration of intravenous antibiotic therapy should be a minimum of 4 to 6 weeks. 6 The length of therapy is dependent on the level of immunocompetence, clinical improvement, and response to treatment demonstrated by subsequent ESR and MRI. 8 The typical treatment of SEA is surgical decompression and drainage in combination with several weeks of antibiotics, 4,13,26 although no consensus on management has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…SEAs are potentially increasing in incidence due to a rise in risk factors (spine trauma, previous skin infections, intravenous drug use, and immunodeficiency) and enhancement of imaging studies allowing increased detection. [1][2][3] Treatment has traditionally been surgical decompression and drainage in combination with antibiotics [4][5][6] ; recent reports suggest that antibiotic therapy alone can be successful in select patient populations. 1,3,[7][8][9][10] We present an institutional review revealing successful outcomes in patients who historically have had significant morbidity and mortality.…”
mentioning
confidence: 99%
“…The association of this pathogen with an epidural abscess has been described in only 4 prior cases, 1,6,7,11 only 2 of which were proven with a surgical biopsy or aspiration of the affected vertebral body or abscess (Table 1). 7,11 Often, cat scratch disease may resolve spontaneously or with medical management; however, the association with a compressive epidural abscess may necessitate surgical intervention. Spinal epidural abscesses have historically been associated with high rates of morbidity and mortality, especially in the pediatric population due to delayed diagnosis and nonspecific symptoms at disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…Tasher et al reported a case of a 5-yearold boy diagnosed with a cervical epidural abscess, treated initially with cloxacillin, gentamicin, and ceftriaxone. 11 However, due to worsening torticollis and evidence of spinal cord compression on follow-up imaging, the patient required surgical decompression. Intraoperative fluid PCR analysis revealed B. henselae.…”
Section: Discussionmentioning
confidence: 99%
“…Rare causes include Clostridium difficile [36] and Cat scratch disease. [37] Inflammation of the intervertebral disk is an uncommon entity. Noniatrogenic cases of diskitis are seen almost exclusively in children and the etiology remains controversial.…”
Section: Pyogenic Vertebral Osteomyelitis and Diskitismentioning
confidence: 99%